Pengaruh Senam Kaki Diabetes Terhadap Sensitivitas Kaki Penderita DM Tipe 2 Di Wilayah Kerja Puskesmas Talawaan - Rizkan H. Djafar; Sarwan Sarwan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Foot sensitivity is very important for people with Diabetes Mellitus because of the risk causing trauma, because there is a decrease in sensitivity, the feet of people with diabetes mellitus often do not feel stimulation, and wounds often occur so that they can make the wound bigger and smelly or diabetic ulcers occur and make sufferers experience a decrease in self-confidence.The purpose of this research is to know the effects of diabetic foot exercise on foot sensitivity of patients for Diabetes mellitus Type 2 at Talawaan Health Centre. This research is quantitative study through using experimental research. Involving the sample of 15 respondents and used the sampling technique with total sampling. Collecting and processing using the Wilcoxon test with P Value of 0.001 with value (? = 0.05). The result of this study indicates that Ha is accepted, and Ho is rejected. The conclusion of study that can be drawn is that there is an effect that foot exercise therapy on has patients with Diabetes Mellitus Type 2 in the Talawaan Health Centre.